133Xe-DSPECT: Bedeutung der zerebrovaskulären Reservekapazität für Diagnostik und Therapie der chronischen zerebralen Ischämie - Leinsinger, G.; Schmiedek, P.; Kreisig, T.; Einhäupl, K.; Bauer, W.; Moser, E. (Nuklearmedizin - NuclearMedicine, 1988)
Using 133Xe-DSPECT, measurements of regional cerebral blood flow (rCBF) were performed before and after stimulation with 1 g of Diamox® in 55 patients with symptomatic occlusion of the internal carotid artery (ICA) and 26 patients without evidence of brain disease (normals). In normals, a negative correlation (r = -0,74) of the Diamox-induced increase of hemispheric blood flow (reserve capacity) and rCBF at rest was observed. In 48 of the 55 patients (87%) with ICA-occlusion a reduced reserve capacity was found. The extent of reduction, however, did not correlate with the findings of transmission CT, because 15 of 21 patients (71 %) with normal CT-scans presented a moderate to severe reduction of reserve capacity. In contrast, reserve capacity corresponded to the extent of arterial collateralisation as documented by cerebral panangiography. In 31 patients EC/IC-bypass surgery was performed. In follow-up studies reserve capacity increased, especially in patients who had a severe reduction preoperatively. Therefore, the combined measurement of rCBF at rest and of reserve capacity is a sensitive, non-invasive method for the diagnosis of (even bilateral) cerebrovascular disease and can be helpful to identify patients with hemodynamic ischemia, who may benefit from EC/IC-bypass surgery.